Are Discrimination and Social Capital Related to Housing Instability?. Issue 1 (2nd January 2017) - Priester, Mary Ann; Foster, Kirk A.; Shaw, Todd C.
Abstract: Existing studies examining social capital and housing instability have overlooked structural factors such as discrimination, providing an incomplete explanation of the relationship between social capital and housing instability. This study addresses this limitation by exploring how discrimination and social capital are related to housing instability. This study is a secondary analysis of data collected during the Atlanta Neighborhood Pilot study. The sample consists of mostly African American adults who resided in the Atlanta metropolitan area in 2013 ( n = 691). After controlling for sociodemographic characteristics, residential mobility, and public assistance, stepwise logistic regression identified social capital and discrimination as significant predictors of housing instability. Lower social capital and higher everyday discrimination scores were associated with increased odds for housing instability. Individuals 35 or older, those with annual incomes between 25, 000 and 50, 000, and those who reported receiving public assistance during their lifetime also had increased odds for housing instability. Findings identify characteristics of individuals vulnerable to housing instability and suggest that social capital development as a housing intervention warrants further exploration. These findings can be utilized by policymakers and practitioners to better target funding and to create efficient systems better equipped to deploy early homelessness prevention interventions.